Potential Benefits of Probiotics for Preterm Infants: A Review - Sarkar, S. (Journal of Nutritional Therapeutics, 2016)
Preterm infants are particularly susceptible to abnormal colonization and are therefore prone to systemic infections due to increased intestinal permeability to potentially pathogens. Abnormal pattern of colonization in pre-term infants may contribute to the pathogenesis of neonatal Necrotizing Enterocolitis (NEC), an acquired gastrointestinal (GI) disease associated with significant morbidity and mortality. Introduction of foods containing probiotic cultures may be advantageous as probiotics prevented gut colonization by abnormal flora. Endeavour has been made to explore the mechanism of gut colonization, suitability of breast milk for preterm infants, effect of administration of probiotics to preterm infants and its safety concerns. Human milk is also suitable for the management of premature infants but fortified breast milk may be a preferred choice and not the pooled pasteurized breast milk. Based upon Randomized Controlled Trials administration of probiotic in preterm infants with a birth weight >1000 g could be recommended due to significantly reduction in incidence of NEC and no systemic infections or serious adverse events was reported. Administration of probiotics in preterm neonates is recommended but further research is emerging for its routine application. Probiotic supplementation in preterm neonates exhibited good safety profile and did not show any side effects and can be recommended for preterm infants but not for extremely low birth weight (ELBW) infants [1, 2].